Analisis Semiotika Roland Bartners Pesan Dakwah Dalam Film Perjalanan Pembuktian Cinta - Ayu Sawitri; Hasan Sazali (Cendekia, 2024)
This study seeks to examine and elucidate the da'wah messages present in the film via the lens of Roland Barthes' semiotic theory. The primary emphasis of the research pertains to communications concerning faith, sharia, ethics, and worship. This research employs a descriptive qualitative methodology, utilizing data collection approaches such as examination of textual content, documents, photographs, and literature review. The acquired data was processed utilizing Nvivo 12 Pro software, which facilitates coding and symbolic interpretation of semiotic aspects in the film. The research findings indicate that the film "The Journey of Proving Love" consistently communicates da'wah messages encompassing faith, sharia, ethics, and worship. Every aspect of preaching is conveyed through visual signs, speech, and narrative, which are examined using Roland Barthes' semiotic approach, elucidating the denotative, connotative, and mythological significance of each symbol in the video. This study demonstrates that the film "The Journey of Proving Love" communicates a da'wah message utilizing Roland Barthes' semiotic framework. The analysis indicates that moral principles, sharia, and faith are interwoven in the speech and relationships among the characters. The moral message is underscored through dialogue that stresses the significance of ethical discourse, while the Shari'a and creed are articulated through the imperative of wearing the headscarf and counsel on fostering a deeper relationship with Allah in personal affairs.